Computing rotational energy transfers of OD−/OH− in collisions with Rb: isotopic effects and inelastic rates at cold ion-trap conditions. (4th December 2015) - González-Sánchez, L; Gianturco, F A; Carelli, F; Wester, R
Abstract: We report close-coupling (CC) quantum dynamics calculations for collisional excitation/de-excitation of the lowest four rotational levels of OD − and of OH − interacting with Rb atoms in a cold ion trap. The calculations are carried out over a range of energies capable of yielding the corresponding rates for state-changing events over a rather broad interval of temperatures which cover those reached in earlier cold trap experiments. They involved sympathetic cooling of the molecular anion through a cloud of laser-cooled Rb atoms, an experiment which is currently being run again through a Heidelberg–Innsbruck collaboration. The significance of isotopic effects is analysed by comparing both systems and the range of temperatures examined in the calculations is extended up to 400 K, starting from a few mK. Both cross sections and rates are found to be markedly larger than in the case of OD − /OH − interacting the He atoms under the same conditions, and the isotopic effects are also seen to be rather significant at the energies examined in the present study. Such findings are discussed in the light of the observed trap losses of molecular anions.